Qualidade da aplicação de inseticida em amendoim (Arachis hypogaea L.), com e sem adjuvantes na calda, sob chuva simulada - Ferreira, Marcelo Da Costa [UNESP]; Lasmar, Olinto; Junior, Sergio Tadeu Decaro; Neves, Samira Scaff; de Azevedo, Letícia Henrique (My University, 2013)
The present work aimed to evaluate the volumetric distribution profiles, droplet spectra, surface tension, contact angle of droplet and the spraying liquid deposition over the peanut leaves (Arachis hypogaea L.), under artificial rain, in comparison with deposition without rain, using two hydraulic nozzle models of plain fan and insecticide spraying liquids with and without adjuvants addition. It were used a patternator for volumetric distribution analysis, a laser particles analyzer to evaluate droplet spectra produced by SF 110015 and XR 110015 nozzles and tensiometer for droplet tension and contact angle. The spraying liquids evaluated were: water, lambda-cialotrina, lambda-cialotrina + nitrogen fertilizer and lambda-cialotrina + mineral oil. All experiments followed a completely randomized design. Data were submitted to variance analysis by F test and the means comparisons by Scott-Knott test at 5% of probability. According to the results, it must be considered the maximum spacing in spray boom usage of 50 and 90 cm between the nozzles SF110015 and XR110015, respectively. The adjuvants effects on droplet spectra have shown addicted to the nozzle and the product used, and the adjuvants addition to the spraying liquid affected the potential risk of drift; The Volumetric Median Diameter (VMD) of produced droplets by nozzles filled into thin class and were not influenced by the adjuvants. The nitrogen fertilizer adjuvant may be indicated to promote improvements on coverage and droplet deposition on target.
Quality of inseticide application on peanut (Arachis hypogaea L.) with and without adjuvants in the spraying liquid, under simulated rain
Keywords: Application technology; Distribution; Droplets; Pulverization; Thrips